Determining drivers of Muslim consumers’ intention to use mobile commerce in Malaysia - Barry, Moussa; Haque, A. K. M. Ahasanul (Kulliyyah of Economics and Management Sciences, 2025)
Abstract: Mobile commerce has rapidly developed in the last few years. However, Muslim consumers’ widespread acceptance of its transactions in Malaysia poses a significant obstacle for m-commerce suppliers. This paper proposes to examine the factors impacting mobile commerce use in Malaysia. Convenience sampling was employed to integrate TAM and TPB, and 350 surveys were collected online from customers residing in Selangor, Malaysia. The current study employed a two-stage structural equation modelling approaches to investigate the research model and evaluate the hypotheses. The results show that perceived usefulness, subjective norms, and perceived ease of use significantly predict Muslim consumers’ intention to adopt m-commerce in Malaysia. In contrast, attitude and perceived behavioural control do not significantly predict their intention to use m-commerce. Hence, the findings of this paper offer significant advantages for m-commerce providers in Malaysia; it is also advantageous for academics, marketers, policymakers, practitioners, and all stakeholders of the industry.